2009
DOI: 10.5194/nhess-9-1403-2009
|View full text |Cite
|
Sign up to set email alerts
|

Ionosperic anomaly due to seismic activities – Part 1: Calibration of the VLF signal of VTX 18.2 KHz station from Kolkata and deviation during seismic events

Abstract: Abstract. VLF signals are long thought to give away important information about the lithosphere-ionosphere coupling. In order to establish co-relations, if any, between the ionospheric activities and the earthquakes, we need to understand what the reference signals are, throughout the year. The best opportunity to do this is during the period of solar minimum where the number of flares and sunspots are negligible and the data would be primarily affected by the sun and variation would be due to normal sunset an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…For a constant long -term statistical analysis, one needs to choose a proper convention to select the terminator time. Say for our previous publications, , Sasmal and Chakrabarti (2009) and as mentioned in Section 1, we have chosen the first minima in sunrise and the last minima during sunset as sunrise and sunset terminator times, respectively. For the phase data, the terminators are highly distinct and there are no secondary minima due to low modal interference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a constant long -term statistical analysis, one needs to choose a proper convention to select the terminator time. Say for our previous publications, , Sasmal and Chakrabarti (2009) and as mentioned in Section 1, we have chosen the first minima in sunrise and the last minima during sunset as sunrise and sunset terminator times, respectively. For the phase data, the terminators are highly distinct and there are no secondary minima due to low modal interference.…”
Section: Discussionmentioning
confidence: 99%
“…This correlation between unusual values of DLPT and DLDT with seismic magnitude shows that the maximum anomaly in the signal occurs on one day before the seismic events. Meanwhile, a statistical study was carried out by Sasmal and Chakrabarti (2009) using the unusual shifts in terminator time by the analysis of a quantity named 'VLF day-length' which is the difference between sunrise and sunset terminator time. In Sasmal and Chakrabarti (2009), it has been reported that the VLF day-length becomes anomalously higher and sometime lower than the normal values during seismic events.…”
Section: Introductionmentioning
confidence: 99%
“…Just after the 2004 devastating earthquake of Indonesia, the seismo-ionospheric correlation was examined by Chakrabarti et al (2005), who came to the conclusion that a definite shift towards the night is present a few days before the earthquake. Subsequently, using the VLF signal from the Indian Navy station VTX (latitude 8.43 • N, longitude 77.73 • E) to Indian Centre for Space Physics (ICSP), Kolkata (latitude 8.43 • N, longitude 77.73 • E), Sasmal et al (2009) showed that the "VLF day length" (defined as the time difference between the two terminator times) becomes anomalously high typically two days before the earthquakes. Subsequently, Ray et al (2010) reported that the "VLF day length" obtained from the VLF signals for VTX-Malda propagation path become anomalously high one day before the earthquake.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…Very Low Frequency (VLF)/Low Frequency (LF) radio sounding is one of the most successful tools for this research. There are several independent findings of anomalies in ELF/VLF/LF signal prior to seismic hazards (e.g., Gokhberg et al, 1989;Hayakawa et al, 1996Hayakawa et al, , 2003Molchanov et al, 1998;Molchanov and Hayakawa, 1998;Clilverd et al, 1999;Hayakawa and Molchanov, 2000;Chakrabarti et al, 2005Sasmal et al, 2009Ray et al, , 2012Ray et al, , 2013. Indian Centre for Space Physics (ICSP) (Lat.…”
Section: Introductionmentioning
confidence: 96%